The Impact of Basic Research on the Quality of Higher Education in Poland: as Reflected in the Program Evaluation Reports of the Polish Accreditation Commission - Hryniewicka-Filipkowska, Wioleta (PRAWO i WIĘŹ, 2025)
The paper is devoted to the analysis of the impact of basic research on the quality of education at the level of higher education in Poland, with particular emphasis on the program evaluation reports of the Polish Accreditation Commission (PKA). The first part of the paper presents the main assumptions of the evaluation of higher education quality in Poland. The extent to which basic research contributes to educational quality standards was then verified. The last part presents the state of practice in the inclusion of basic research in the process of program evaluation by PKA. This discussion is based on an analysis of program evaluation reports for the faculty of law. The author seeks answers to the following questions: Does the law enforce the inclusion of basic research in PKA program evaluation? And does practice implement the law's requirements to include basic research in PKA’s program evaluation? The study was created as a result of the research project entitled Impact of legal basic research on legal education on the example of basic research funded by the National Science Center in Poland No. 2021/41/B/ HS5/0331 (NCN). The scientific purpose of the project is to analyze and evaluate the impact of NCN-funded basic research in the legal sciences, conducted by academics, on the education of lawyers at public universities in Poland.